PENGEMBANGAN MEDIA TAKTIK (KOTAK TEMATIK) MODEL NUMBER HEAD TOGETHER TEMA DIRIKU KELAS 1 SEKOLAH DASAR - Diyah Nur Fadilah; Rahmat Rais; Diana Endah Handayani (Universitas Negeri Medan, 2018)
Abstract : Development of Media Taktik (Kotak Tematik) Model Number Head Together Theme Of Me Grade 1 Elementary School. The study aims determine the feasibility of products, teacher and student response on the development of media Thematic Box. This type of research is research and development. The population this research is the students of first grade students of Supriyadi Elementary School Semarang amounting 34 students. The data obtained through teacher response, student, the validation of material and media experts. The result of development in the form of media product Thematic Box. The data processing is from the of material expert I 85% very feasible, the material expert II is 80% feasible, the media expert I is 79.68% feasible, the media expert II 78.125% is feasible, the teacher's response question 96% is very positive, 89,01% is very positive. The conclusion this research Thematic Box can be used as thematic learning.Keywords: Kotak Tematik, Number Head TogetherAbstrak : Pengembangan Media Taktik (Kotak Tematik) Model Number Head Together Tema Diriku Kelas 1 Sekolah Dasar. Penelitian bertujuan untuk mengetahui kelayakan produk, respon guru dan siswa pada pengembangan media Kotak Tematik. Jenis penelitian adalah penelitian dan pengembangan. Populasi dalam penelitian adalah siswa kelas I SD Supriyadi Semarang berjumlah 34 siswa. Data diperoleh melalui hasil respon guru, siswa, validasi ahli materi dan media. Hasil pengembangan berupa produk media Kotak Tematik. Pengolahan data dari ahli materi I 85% sangat layak, ahli materi II 80% layak, ahli media I 79,68% layak, ahli media II 78,125% layak, angket respon guru 96% sangat positif, angket respon siswa 89,01% sangat positif. Kesimpulan media Kotak Tematik dapat digunakan sebagai media pembelajaran tematik.Kata Kunci: Kotak Tematik, Number Head Together.